Effects of a microbubble ultrasound contrast agent on high-intensity focused ultrasound for uterine fibroids: a randomised controlled trial. (17th November 2018) - Chen, Yan; Jiang, Jing; Zeng, Yuhua; Tian, Xiaobing; Zhang, Miao; Wu, Hong; Zhou, Honggui
Abstract: Objective: To investigate the effects of a microbubble ultrasound contrast agent on high-intensity focused ultrasound (HIFU) treatment of uterine fibroids. Methods: A total of 120 patients with solitary uterine fibroid were randomly assigned into Groups A, B, C and D. Patients in Groups A and B received 1.5 ml of SonoVue, Groups C and D received 1.5 ml of saline before HIFU ablation. HIFU sonication started at 6 min after administration of SonoVue or saline in Groups A and C, whereas it started at 10 min in Groups B and D. On day 1 after HIFU, magnetic resonance imaging was performed. Patients were followed up via phone or clinic visit during the first week after HIFU. Results: No significant difference was observed in terms of age, fibroid location, diameter of fibroids, signal intensity on T2-weighted imaging, or tumour volume among the four groups ( p  > 0.05). The use of SonoVue significantly shortened the treatment time and sonication time. The sonication start time of 6 min, relative to 10 min, had significant effects on the treatment time and sonication time. The use of intravenous SonoVue followed by HIFU ablation 6 min later significantly increased the rate of significant grey-scale changes (55.9%) and the non-perfused volume ratio (94.2% ± 10.6%). No significant differences were observed in the incidence of intra-procedure and post-HIFU adverse effects among the four groups ( p  > 0.05). Conclusions: SonoVue could be safely used to enhance the ablation effects of HIFU treatment of uterine fibroids.